Respiratory syncytial virus hospitalization costs, rates, and seasonality in Asia: a systematic review and meta-analysisResearch in context - Luis J. Ponce; Thaddaeus Wu; Darren Junfeng Sim; Jo Yi Chow; Liang En Wee; Po Ying Chia; David Chien Boon Lye; Yee-Sin Leo; Jue Tao Lim (EClinicalMedicine, 2025)
Summary: Background: RSV is a major cause of morbidity and a large public health threat, yet its burden in Asia remains poorly characterized, limiting effective public health planning. This study's objectives were to systematically review RSV hospitalization rates, seasonality, and medical costs in Asia. Methods: We conducted a systematic review and meta-analysis, searching five major public health databases (PubMed, Cochrane Library, Web of Science, Embase, Scopus) for peer-reviewed articles published from January 2005 to the last search date of 16 April 2025. Studies reporting RSV incidence, hospitalization rates, costs, or seasonality in Asia were included, regardless of healthcare setting or study design. Exclusions included studies without primary data, data from outside of Asia, and those lacking clear RSV case definitions. Two independent reviewers performed data extraction and quality assessment using JBI and TRIPOD critical appraisal tools. A meta-analysis and publication bias analysis of mean direct medical costs was performed. Data were synthesized by seasonality, costs, and hospitalization rates. Findings: Of 1231 screened studies, 159 met inclusion criteria. RSV seasonality varied: temperate regions showed winter peaks, while tropical regions had more variable patterns. RSV-associated hospitalization rates ranged widely, from 0.42 per 1000 person-years among the elderly in Thailand to 124 per 1000 children-years among infants <2 years in the Philippines. Overall, rates declined with age. RSV direct inpatient medical costs ranged from US$126–2448 in LMICs to US$838–3402 in high-income countries. 104 (65%) of studies were classified as having a low risk of bias, while 55 (35%) received a moderate risk of bias score. Interpretation: This study highlights the significant burden of RSV in Asia, particularly among young children, and highlights substantial variation in seasonality and economic impact across the region. The findings emphasize the need for region-specific RSV data to inform targeted prevention strategies and healthcare resource allocation. High heterogeneity in cost estimates suggests variability in healthcare access and economic conditions, warranting further investigation. Funding: Jue Tao Lim is supported by the Lee Kong Chian School of Medicine—Ministry of Education Start-Up Grant. YSL is funded by the National Centre for Infectious Diseases Department Research Fund.